(3GdJUQjM HTQM GdJhVjMs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3MSjf Hf eMeO Hf SdjeGf GdTGaYj GdCTYQj hQecGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3Ef GdTQM GdeTJgQ HGdJhVjM Ydi CdajI GHf eGdc aj GdfMh ddTjN GdEeGe GdYdGeI GdQHGfj LeGd GdOjf CHj eMeO YHO Gddg Hf jhSa Hf gTGe GdCfUGQj (B...s
(3BNQgG (B:s
... (3hZjQ Pdc eeG LGA HGdGXgGQ GdJVYja dHjGf GdCUd cGdbhO HGdJUMjM Ch aj VQhQI cbhdg hgh GHh GdfLe GdYLdj (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B2\297s
(3CSeGA GdcJH GdeJee dcTa GdXfhf dQjGV RGOg (B94s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs